Wage Level Survey in Croatia in Comparison to Countries of the Region and the EU from 2011-2019 - Stela PRVONOŽEC; Anita PEŠA; Berislav BOLFEK (Communications of International Proceedings, 2020)
The level of wages and their ability to cover the cost of living is a key issue for both employees and economic policy makers. In some cases, wages paid to a worker are not sufficient to cover the average cost of living, which is especially relevant in Croatia, Bosnia and Herzegovina, Serbia and Montenegro, so the topic of this paper is the level of wages in Croatia, Bosnia and Herzegovina, Serbia and Montenegro in the period from 2011to 2019 and comparing them with the EU. The survey is based on Eurostat data and authors calculations. The average monthly net salary is not sufficient to cover the average cost of living in Croatia, Bosnia and Herzegovina, Serbia and Montenegro. The observed countries record significantly lower levels of purchasing power and living standards compared to other European countries, and achieving stronger economic growth has been hampered by inefficient economic policies. The corona crisis will have a profound effect on the economy of these countries.
Keywords: Croatia; wage levels; cost of living; countries of the region.